Comparison of Chromia Growth Kinetics in a Ni-based Superalloy, with and without Shot-peening. (November 2015) - Cruchley, S.; Taylor, M.P.; Ding, R.; Evans, H.E.; Child, D.J.; Hardy, M.C.
Highlights: Two alloy surface treatments are compared. The kinetics of a Ni-based superalloy are compared to pure chromia formation. The enhancement is described in terms of Ti-doping of the surface chromia scale. For the first time, a (Ta, Ti)O2 phase, formed at the oxide metal interface, is identified. Abstract: The effect of shot-peening on the oxidation in air of the Ni-based superalloy RR1000 has been investigated over the temperature range 700–800 °C. The surface oxide in both peened and un-peened conditions consisted of isolated grains of rutile on the outermost surface beneath which was a protective Ti-doped chromia scale. Internal oxidation of aluminium occurred within the alloy with the formation of alumina particles within a γ ′ (nominally Ni3 (Al, Ti)) denuded zone but the morphology of the sub-surface oxides differed between the two surface conditions examined. The kinetics of thickening of the chromia layer were sub-parabolic in most cases but closely approached parabolic behaviour for the un-peened surface condition at 800 °C. An enhancement in the rate of chromia growth was found for both surface conditions compared with a Ti-free chromia layer. This enhancement has been attributed to increased Cr ion diffusion as a result of Ti-doping of the chromia layer but the effect is reduced over time because of Ti-depletion in the alloy. At 800 °C, in the un-peened condition, the reduction in growth rate with exposure time is much less marked and this effect seems to be associated with the formation of a (Ti, Ta)O2 phase beneath the chromia layer.